Gestão democrática da escola pública : a participação como princípio da democracia - Marcato, Célio Tiago (Universidade Federal de São Carlos, 2017)
This paper analyzes the basis of participation, as a principle of citizenship and democracy, in order to understand its limits and possibilities when they are applied to educational processes, especially those referring to the democratic management of the public school. For this, conceptual investigations of categories related to the theme of participation were made, including the presuppositions of democracy. They were examined: the theories of the forms of government, highlighting the difference between the Greek and current democracy and the tripartition of powers; the theories of democracy, exploring its definitions, the issue of scale, the criteria and its intrinsic problems; the citizenship, seeking to show its conceptual basis present in the legislations regulating school education and democratic management of the public school; finally, the basis of education related to the democratic management of the public school, analyzing categories inherent to the principle of participation. As theoretical research, the purpose of this paper was to build an articulation of concepts derived from political theory and education, concerning to the participation as the basis of democracy in the society and at school and from the democratic management of the public school. It was possible to conclude that an approximation of studies of political science and education is unavoidable, since democracy and participation are common categories in two fields. It was also possible to determine that there is a possibility of progressing in mechanisms of direct participation in the democratic management of the school, making it more effective, contrary to the decorative participation, established when trying to transpose the private business management premises to the school.
Keywords: Democracia; Gestão democrática; Escola pública; Participação; Democracy; Democratic management; Public school; Participation; CIENCIAS HUMANAS::EDUCACAO